This is a super easy Q that I need an explanation for so anyone who is nice enough plz answer it!!!
y = 3x + 3
y = x − 1
Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form.

Respuesta :

Since y equals both those expressions the expressions equal each other

3X+3= X-1

Subtract X from both sides

2X+3= -1

Subtract 3 from both sides

2X= -4

Divide by 2 on both sides

X= -2

Substitute X, which is -2, in one of the equations. I'll use y= X-1

y= -2-1

y= -3

Your final answer is (-2, -3)
ACCESS MORE